THE IMPROVEMENT OF RAMIE FIBER PROPERTIES AS COMPOSITE MATERIALS USING ALKALIZATION TREATMENT: NaOH CONCENTRATION - Umi Lailatul Jamilah; Sujito Sujito (Jurnal Sains Materi Indonesia, 2021)
THE IMPROVEMENT OF RAMIE FIBER PROPERTIES AS COMPOSITE MATERIALS USING ALKALIZATION TREATMENT: NaOH CONCENTRATION. Ramie fiber is a plant fiber that has good quality and potential as a constituent of composite materials. In this study, ramie fiber surface modification was conducted through alkalization with various at 0%, 4%, 5%, 6%, 7%, 8%, and 9% concentrations of NaOH using a magnetic stirrer with a speed of 200 rpm at 70οC for 5 hours. Alkaline ramie fibers are characterized using the Cheson method to determine the chemical composition of ramie fiber, FT-IR test to determine the function group of ramie fiber, morphological test to know the surface structure and diameter of ramie fiber, as well as tensile test to know the tensile strength and tensile modulus of PLA/ramie composite. Overall, the increase of NaOH concentration up to 8% percentage was able to increase the level of cellulose and lignin ramie fibers by 88.180 % and 2.444 %, as well as lower hemicellulose levels of 1.446 %. The alkalization treatment of 8% NaOH, optimally reduces the hydrophilic properties of the fiber. The increased concentration of NaOH makes the fiber surface cleaner and the diameter smaller, but the fiber structure is damaged at a concentration of NaOH more than 8%. Tensile test results showed that alkalized ramie fibers with an 8% concentration of NaOH produced PLA/ramie composites with the highest tensile strength and tensile modulus of 57.37 MPa and 248.25 MPa. Thus, the optimum ramie fiber properties are increased using alkalization with an 8% concentration of NaOH.